Inorganic spectroscopic methods - Brisdon, Alan K. (91p Oxford University Press, 1998)
An understanding of spectroscopic methods is a pre-requisite for students in chemistry and related disciplines from the undergraduate level onwards. Inorganic Spectroscopic Methods provides a firm introduction to common spectroscopic techniques and interpretation of spectra, and their application to inorganic-based systems.The approach taken is unashamedly aimed at the application of the techniques and interpretation of the spectra obtained. Worked examples, illustrative diagrams and references for a theoretical approach are provided throughout the book. Beginning with a introductory description of electromagnetic radiation and its interaction with matter, each subsequent chapter covers the physical basis of related spectroscopic methods (vibrational, resonance, UV-visible spectroscopy, mass spectrometry) and their applications typical in inorganic compounds. Each chapter ends with a number of set problems and short questions in the margin are given throughout the chapters to test the basic concepts. The final chapter offers an integrated approach to the identification of unknown materials - putting together the techniques discussed. This essential text for all undergraduate chemists will also benefit postgraduates in chemistry, and undergraduate and postgraduate students of biochemistry and the biomedical sciences.
Keywords: chemistry; inorganic chemistry; spectroscopic